GENDER DALAM MATERI BELAJAR BAHASA ARAB DI PESANTREN - Ismail Suardi Wekke (Turast: Jurnal Penelitian dan Pengabdian, 2013)
Pesantren (boarding school) shows a significant contribution on the Indonesian educational system throughtime to time. This fact shows that pesantren has a main focus of education activites. Therefore, this article willcopare how the Arabic language material in two schools of woman and man. Research was conducted in SouthSulawesi employing qualitative approach. In-depth interview and nonparticipant observation were appliedthrough data collection. Nine months data collection and analysis was needed to perform this research. Itwas from September last year to March 2013. Research shows there are many Learning material in any caseswill depend to the school environment. This paper finds out following: first, description of the items practicedin Pesantren IMMIM in term of language learning material and gender. Second is to describe elementarydescription of language learning material that choosen by teachers in both pesantrens. Learning material wasfinalized started from teacher board. Then, they examine it to management level. On the end of process, thecurriculum was consultated to many stakeholders. Finally, the differences between two schools were constructedfrom environment, tradition, and learning objective. Learning environment as a part of teaching and learningwere a classroom at large. It helps students and teacher to acquire the language.